Are phenotypic disparity and rate of morphological evolution correlated with ecological diversity in Carnivora?. (10th May 2018) - Michaud, Margot; Veron, Gèraldine; Peignè, Stèphane; Blin, Amandine; Fabre, Anne-Claire
Abstract: In the modern definition of adaptive radiation, a clade rapidly diversifies from a common ancestor to colonize a wide variety of new ecological niches. The idea of multiplication of species related to an adaptive radiation is well accepted. However, the assessment of how ecological and phenotypic diversity is interrelated in the case of adaptive radiation has rarely been studied. This is the background of the present paper, which aimed to test the correlation between phenotypic disparity and the rate of morphological evolution in relationship to ecological diversity in terrestrial Carnivora. To do so, we used geometric morphometrics to investigate skull shape disparity and the rate of morphological evolution at the family level in Carnivora. Our analyses highlight a correlation between ecological diversity and phenotypic disparity and demonstrate that the skull shape is impacted by ecology. On the contrary, our data do not provide any correlation between ecological diversity and the rate of morphological evolution, nor between phenotypic disparity and the rate of morphological evolution. We suggest that this absence of correlation could be explained by a contrasting tempo and a shift in morphological evolutionary rate among families.